1994
DOI: 10.2307/3235977
|View full text |Cite
|
Sign up to set email alerts
|

Influence of landscape complexity and land management on woody plant diversity in northern Spain

Abstract: . Changes in land use, particularly the type of forest management, and their spatial pattern, especially woody plant diversity, were related to each other in an area in the Basque region (Spain). The number and diversity of boundaries between landscape patches is related to the development of the spatial complexity of the landscape, C(s), measured in bits and defined as: C(s) = H(b) H(l), where H(b) is the boundary diversity H(1) the spatial heterogeneity generated by these boundaries. As to the vegetation ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 52 publications
1
36
0
1
Order By: Relevance
“…Sanguin et al (2009) showed that Verrucomicrobia was one of the prevalent phyla during the outbreak of wheat take-all disease, which was different from the finding in the present study that the abundance of this phylum was higher in healthy (5.06 % in rhizosphere soil and 0.40 % in roots) than diseased plants (2.85 % in rhizosphere soil and 0.32 % in roots). This may be explained by the low relative abundance of Verrucomicrobia accounted for the total sequences, 3.96 % in rhizosphere soil and 0.36 % in roots on average, variation in the initiator of different soil-borne diseases (Van Elsas et al 2002) and difference in land management (Rescia et al 1994). In this study, high abundance of Pseudomonas, which was also isolated from rotted root of P. notoginseng and exhibited the strongest pathogenicity (Miao et al 2006), was identified both in rhizosphere soils and roots, and was more abundant in diseased than that in healthy plants (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Sanguin et al (2009) showed that Verrucomicrobia was one of the prevalent phyla during the outbreak of wheat take-all disease, which was different from the finding in the present study that the abundance of this phylum was higher in healthy (5.06 % in rhizosphere soil and 0.40 % in roots) than diseased plants (2.85 % in rhizosphere soil and 0.32 % in roots). This may be explained by the low relative abundance of Verrucomicrobia accounted for the total sequences, 3.96 % in rhizosphere soil and 0.36 % in roots on average, variation in the initiator of different soil-borne diseases (Van Elsas et al 2002) and difference in land management (Rescia et al 1994). In this study, high abundance of Pseudomonas, which was also isolated from rotted root of P. notoginseng and exhibited the strongest pathogenicity (Miao et al 2006), was identified both in rhizosphere soils and roots, and was more abundant in diseased than that in healthy plants (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Another contributing factor to higher diversity at lower belts may be the higher surface area of the mentioned belts (Wang et al 2007). The complexity behind the diversity patterns, especially in temperate systems including Hyrcanian forest and European deciduous forests has been pointed out by several authors (see Rescia et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, topography interacts with local wind direction, microclimates and, in turn, vegetation type, fuel loads and moisture content. Several studies have shown topographic influences on vegetation composition and structure (Fontaine et al, 2007;Rescia et al, 1994), transpiration and desiccation conditions (Rana et al, 2005;Van der Trol et al, 2007), vegetation dynamics (Carmel andFlather, 2004;Mouillot et al, 2005), fire severity (Broncano and Retana 2004), and post-fire vegetation regeneration (Peñuelas et al, 2007;Baeza et al, 2007). Furthermore, some of the observed topographic effects on fire occurrence can be explained by human activities (e.g.…”
Section: Fire Hazard Is Higher In Specific Topographic Locationsmentioning
confidence: 99%